Keuangan Negara: Reformulasi Kriteria Proyek Dalam Rangka Klasifikasi Anggaran Pengeluaran - Bambang Nugroho (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1997)
A distinctive classification should be applied to government budget, particularly between budget allocation for consumption and for investment. This is important for policy makers so that they will be able to forecast investment and consumption effects on economic growth and inflation. In Indonesian budget system, unclear criteria to distinguish routine and development budget also creates many problematic situations in managing public finance. This article offers some alternatives to solve the problem. One simple solution is to reformulate what is the so-called projects. Projects are an activity or a group of activities which has certain goals and objectives, attains to result new physical or non-physical assets in the form of goods, services or capability improvements. Those activities are managed whithin certain span of time and amount of fund. Instead of consumptions, projects are primarily investments. If this alternative is implemented consistently in the budget allocation systems, it may decrease the figure of government saving and number of Project List Proposal (Daftar Isian Proyek - DIP), which may not be favorable for implementors who have vested interest. By doing so, however, overlapped activities which are funded by routine and development budget can be avoided substantially. Government accounting system would be more efficient because every projects should be resulted in investment. A more radical approach is to invalidate the distinction between routine and development (non-routine) budget allocation by all means. Productivity and accountability would be the main criteria for all forms of the government fund allocation. There should be a fundamental change in the government budget cycle. Government saving should be formulated into: the subtraction between domestic revenue and additional finance (belanja penunjang), and T-account system in the government budget (APBN) should be substantially modified. Finally, all of these remedies depend on effort to distinguish clearly between routine and project criteria through a transparent definition and vision of those who manage the budget allocation system.